ANALISIS KEBISINGAN PADA INSTITUSI PENDIDIKAN DI FRONTAGE ROAD SISI TIMUR JALAN A.YANI SURABAYA - Widya Nilandita; Dyah Ratri Nurmaningsih; Shinfi Wazna Auvaria (Al-Ard: Jurnal Teknik Lingkungan, 2018)
Noise can occur anywhere, including at educational institutions. Noise research at educational institutions began to be studied a lot because of the negative impact on the teaching and learning process and disrupt the performance of teachers and students. Some studies show that schools or universities located on the edge of the road, show noise levels that exceed quality standards. This research was conducted at educational institutions located along the east Frontage Road Jl A.Yani Road, Surabaya, by measuring noise levels at 3 locations, in daylighting measurements with 4 measurement times (L1-L4). Data collection and processing was carried out by referring to the quality standard of KEPMENLH No. 48 of 1996. Data was measured using a sound level meter for 10 minutes for each measurement, with a reading every 5 seconds to obtain 120 data. Data processing results are compared with the standard noise level. The noise value at SD Margorejo I / 403 is 82.2 dB, UIN Sunan Ampel Surabaya is 79.76 dB, and SMK 3 Surabaya is 80.06 dB. The noise level value has exceeded the established quality standard, which has maximum of 55 dB for the educational intitutions area. The source of noise comes from the activities of motorized vehicles in and around educational institution that is quite crowded. Another cause of the high noise value is the train activities along the east frontage road Jl A.yani Surabaya, as well as the distance of the noise source with research location that relatively close. Keywords: noise, educational institution, sound level meter